Escenarios y normas de aplicabilidad en un modelo de enseñanza y aprendizaje 2.0 con el uso de blogs y microblogs - Checa García, Fernando (Nómadas. Critical Journal of Social and Juridical Science, 2015)
The use of blogs as a tool for the creation and dissemination of knowledge has emerged in recent years as one of the most interesting ways to work in learning environments. Working with blogs offer for schools and universities not only open lines for a different way of teaching and learning, but for a large change in the relationship of schools with their environment. In this paper we analyze the different usage scenarios that may have blogs when it applied from a methodological point of view using a model defined in different educational ways. We also analyze and expose different rules than a model with these characteristics should be considered for obtaining positive and measurable results.